Design, Bioanalytical, and Biomedical Applications of Aptamer-Based Hydrogels - Di, Ya; Wang, Ping; Li, Chunyan; Xu, Shufeng; Tian, Qi; Wu, Tong; Tian, Yaling; Gao, Liming (Frontiers in Medicine, 2020)
Aptamers are special types of single-stranded DNA generated by a process called systematic evolution of ligands by exponential enrichment (SELEX). Due to significant advances in the chemical synthesis and biotechnological production, aptamers have gained significant attention as versatile building blocks for the next generation of soft materials. Hydrogels, is a kind of high water-retainable materials with three-dimensional (3D) polymeric network. Aptamers as the vital element has greatly expanded the applications of hydrogels. Due to their biocompatibility, selective binding, and molecular recognition, aptamer-based hydrogels can be utilized for bioanalytical and biomedical applications. In this review, we focus on the latest strategies of aptamer -based hydrogel in bioanalytical and biomedical applications. We begin this review with an overview of the underlying design principles for the construction of aptamer -based hydrogels. Next, we will discuss some bioanalytical and biomedical applications of aptamer -based hydrogel including biosensing, target capture and release, logic devices, gene and cancer therapy. Finally, recent progresses of aptamer -based hydrogel are discussed with their challenges and future perspectives.